2005
DOI: 10.1021/la050018t
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Examination of Mesophases Formed by DMPC and DHPC Mixtures

Abstract: Mixtures of long- and short-chain phospholipids, specifically 14:0 and 6:0 phosphatidylcholines (DMPC and DHPC), have been used successfully in NMR studies as magnetically alignable substrates for membrane-associated proteins. However, recent publications have shown that the phase behavior of these mixtures is much more complex than originally thought. Using polarized light microscopy and small-angle neutron scattering, phase diagrams of DMPC/DHPC mixtures at molar ratios of 2, 3.2, and 5 have been determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
150
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(161 citation statements)
references
References 41 publications
9
150
1
Order By: Relevance
“…From numerous NMR studies, it was initially believed to be bicelles, but was later shown, by SANS, to be consistent with perforated lamellae (Nieh et al 2002). However, most recently SANS, POM and cryo-TEM studies (Nieh et al 2002;Harroun et al 2005;van Dam et al 2004) have shown that the magnetically alignable phase of nondoped bicellar mixtures is in fact characterized by worm-like micelles (Nieh et al 2004a). The nondoped mixtures and their various morphologies have been used extensively in structure-function studies of membrane associated proteins and protein crystallization (see Sect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From numerous NMR studies, it was initially believed to be bicelles, but was later shown, by SANS, to be consistent with perforated lamellae (Nieh et al 2002). However, most recently SANS, POM and cryo-TEM studies (Nieh et al 2002;Harroun et al 2005;van Dam et al 2004) have shown that the magnetically alignable phase of nondoped bicellar mixtures is in fact characterized by worm-like micelles (Nieh et al 2004a). The nondoped mixtures and their various morphologies have been used extensively in structure-function studies of membrane associated proteins and protein crystallization (see Sect.…”
Section: Discussionmentioning
confidence: 99%
“…The recent report of Harroun et al (2005) provides a nearly comprehensive study of bicellar mixture mesophases, reconciling a number of conflicting views. The phase diagram shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, bilayered ribbons (Fig. 12c) and perforated lamellae were found in neutral and charged systems, respectively (Nieh et al, 2004;Harroun et al, 2005;Katsaras et al, 2005). The ribbons transformed into MLVs with increasing temperature, while the charged perforated lamellae remained unaltered.…”
Section: "Bicelle" Mixtures: Resultant Morphologiesmentioning
confidence: 98%